HMGA1 and FOXM1 Cooperate to Promote G2/M Cell Cycle Progression in Cancer Cells - Qingfang Zheng; Ziyang Luo; Mingjun Xu; Shazhou Ye; Yuxin Lei; Yang Xi (Life, 2023)
HMGA1 is a chromatin-binding protein and performs its biological function by remodeling chromatin structure or recruiting other transcription factors. However, the role of abnormally high level of HMGA1 in cancer cells and its regulatory mechanism still require further investigation. In this study, we performed a prognostic analysis and showed that high level of either HMGA1 or FOXM1 was associated with poor prognosis in various cancers based on the TCGA database. Furthermore, the expression pattern of HMGA1 and FOXM1 showed a significant strong positive correlation in most type of cancers, especially lung adenocarcinoma, pancreatic cancer and liver cancer. Further analysis of the biological effects of their high correlation in cancers suggested that cell cycle was the most significant related pathway commonly regulated by HMGA1 and FOXM1. After knockdown of HMGA1 and FOXM1 by specific siRNAs, an obvious increased G2/M phase was observed in the siHMGA1 and siFOXM1 groups compared to the siNC group. The expression levels of key G2/M phase regulatory genes PLK1 and CCNB1 were significantly downregulated. Importantly, HMGA1 and FOXM1 were identified to form a protein complex and co-located in the nucleus based on co-immunoprecipitation and immunofluorescence staining, respectively. Thus, our results provide the basic evidence that HMGA1 and FOXM1 cooperatively accelerate cell cycle progression by up-regulating PLK1 and CCNB1 to promote cancer cell proliferation.